Protein Intake Influences the Incidence of Anemia in Female Students at Sidoarjo Islamic Middle School - Maemonah, Siti; Suprihatin, Kusmini; Siagian, Hotmaida (Poltekkes Kemenkes Palu, 2025)
Anemia is a health problem that can occur in all age groups from toddlers to old age. Young women are susceptible to suffering from anemia because they experience a menstrual cycle every month. This study aims to determine the influence of age, menstrual pattern, nutritional adequacy rate (energy adequacy rate and protein adequacy rate), and nutritional status on the incidence of anemia in female students at Sidoarjo Islamic Middle School. The design of this research is observational analytic with a cross sectional approach. The population was female students at Sidoarjo Islamic Middle School with a sample size of 53 people. The independent variables in this study were age, menstrual pattern, nutritional adequacy rate (energy adequacy rate and protein adequacy rate), and nutritional status; and dependent variable is anemia. Data collection was carried out by checking Hb and Hct levels, measuring body weight and height, and filling out questionnaires. The collected data was analyzed using path analysis using smart Partial Least Square (PLS). There is a significant effect of protein adequacy on hemoglobin (Hb) levels. Female students with adequate protein intake tend to have better Hb levels, which play a role in preventing anemia. Therefore, meeting optimal protein needs is very important to support blood health and prevent health problems in female students.